From the solid waste mixture of coal hydrogasification residue and red mud to efficient Fe3O4/C- and Fe/C-based composite microwave absorbents. (January 2023) - Liang, Liping; Zhang, Jinpeng; Wang, Yake; Gao, Xuzhou; Su, Ningjing; Shi, Shuping; Zhang, Rong; Li, Guomin
Abstract: Following the concept of sustainable development, magnetic particles/C-based composite microwave absorbing materials were prepared through reactions between two solid wastes: coal hydrogasification residue (CHR) and red mud (RM). At a fixed mass ratio of CHR to RM of 0.6:1, Fe3 O4 /C- and Fe/C-based composites could be obtained at 700 and 900 °C, respectively. A minimum microwave reflection loss of −48.3 dB and a largest effective absorption bandwidth of 4.5 GHz were achieved for the Fe/C-based composite with a simulated thickness of 1.5 mm. The Fe3 O4 /C-based composite exhibited slightly poorer performance because the fixed initial system could not guarantee impedance matching for both products. The strong intrinsic attenuation capacity of the materials mainly resulted from the dielectric loss, including conduction loss caused by graphite carbon as well as interfacial polarization relaxation loss arising from the numerous phase boundaries. Graphical abstract: Image 1 Highlights: Solid wastes were recycled to construct materials to control microwave pollution. Fe3 O4 /C- and Fe/C-based composites both possess excellent absorption performance. Impedance matching and dielectric loss play a key role to performance. Graphite carbon and phase boundaries give rise to dielectric loss. Reactions among Na2 O, SiO2 and Al2 O3 can weaken the alkalinity from red mud.